Postprandial amino acid, glucose and insulin responses among healthy adults after a single intake of Lemna minor in comparison with green peas: a randomised trial. (2019) - Zeinstra, Gertrude G.; Somhorst, Dianne; Oosterink, Els; Fick, Henriette; Klopping-Ketelaars, Ineke; van der Meer, Ingrid M.; Mes, Jurriaan J.
Abstract: A high protein content combined with its enormous growth capacity make duckweed an interesting alternative protein source, but information about postprandial responses in humans is lacking. The present study aimed to assess the postprandial serum amino acid profile of Lemna minor in healthy adults in comparison with green peas. A secondary objective was to obtain insights regarding human safety. A total of twelve healthy volunteers participated in a randomised, cross-over trial. Subjects received two protein sources in randomised order with a 1-week washout period. After an overnight fast, subjects consumed L. minor or peas (equivalent to 20 g of protein). After a baseline sample, blood samples were taken 15, 30, 45, 60, 75, 90, 120, 150 and 180 min after consumption to assess amino acid, glucose and insulin levels. Heart rate, blood pressure and aural temperature were measured before and after consumption, and subjects reported on gastrointestinal discomfort for four subsequent days. Compared with green peas, significantly lower blood concentrations of amino acids from L. minor were observed, indicating lower digestibility. L. minor consumption resulted in lower plasma glucose and insulin levels compared with peas, probably due to different glucose content. There were no significant differences concerning the assessed health parameters or the number of gastrointestinal complaints, indicating that a single bolus of L. minor – grown under controlled conditions – did not induce acute adverse effects in humans. Further studies need to investigate effects of repeated L. minor intake and whether proteins purified from L. minor can be digested more easily.